2019
DOI: 10.1002/stem.3008
|View full text |Cite
|
Sign up to set email alerts
|

PDGF Signaling in Primitive Endoderm Cell Survival Is Mediated by PI3K-mTOR Through p53-Independent Mechanism

Abstract: Receptor tyrosine kinase signaling pathways are key regulators for the formation of the primitive endoderm (PrE) and the epiblast (Epi) from the inner cell mass (ICM) of the mouse preimplantation embryo. Among them, FGF signaling is critical for PrE cell specification, whereas PDGF signaling is critical for the survival of committed PrE cells. Here, we investigated possible functional redundancies among FGF, PDGF, and KIT signaling and showed that only PDGF signaling is involved in PrE cell survival. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Or additionally, by upregulation of RTK receptors FGFR2 and PDGFRA or modifiers of the pathway upon PrE specification (Azami et al, 2019;Kang et al, 2017;Molotkov et al, 2017). Although, as both FGFR2 and PDGFRA act via the PI3K axis for PrE-survival (Bessonnard et al, 2019;Molotkov and Soriano, 2018;Artus et al, 2013), ERK activity is likely relayed by FGFR1, which is the predominant receptor for PrE specification (Kang et al, 2017;Molotkov et al, 2017). Therefore, it remains possible that, even though they are subtle, the higher ERK activities seen here in the PrE might be instructive for lineage acquisition.…”
Section: Discussionmentioning
confidence: 90%
“…Or additionally, by upregulation of RTK receptors FGFR2 and PDGFRA or modifiers of the pathway upon PrE specification (Azami et al, 2019;Kang et al, 2017;Molotkov et al, 2017). Although, as both FGFR2 and PDGFRA act via the PI3K axis for PrE-survival (Bessonnard et al, 2019;Molotkov and Soriano, 2018;Artus et al, 2013), ERK activity is likely relayed by FGFR1, which is the predominant receptor for PrE specification (Kang et al, 2017;Molotkov et al, 2017). Therefore, it remains possible that, even though they are subtle, the higher ERK activities seen here in the PrE might be instructive for lineage acquisition.…”
Section: Discussionmentioning
confidence: 90%
“…These observations suggest that (i) other input signals regulate MEK activity and (ii) one or multiple additional downstream effectors control the EPI/HYPO genetic program. For example, platelet-derived growth factor (PDGF) signaling is critical in regulating HYPO cell survival through the PI3K-mTOR pathway in mice (Artus et al 2010, Bessonnard et al 2019.…”
Section: Epi/hypo Specificationmentioning
confidence: 99%
“…We measured the protein levels of AKT, MAPK, STAT3, P70S6, and AMPK, as well as their active (phosphorylated) forms (Figures 3A and 3B). These pathways are selected because their established roles in pluripotency and/or blastocyst development (Bell and Watson, 2013; Bessonnard et al, 2019; Bora et al, 2021; Calder et al, 2017; Hatakeyama, 2012; Murakami et al, 2004; Riley et al, 2005). Our results revealed that the ratios of p-AKT/AKT, p-MAPK/MAPK, p-P70S6/P70S6 were significantly higher in blastoids than non-blastoid structures, suggesting PI3K/AKT, MAPK and mTOR pathways play important roles during blastoid formation.…”
Section: Resultsmentioning
confidence: 99%